Epidemiology of Multiple Chronic Conditions: An International Perspective. Issue 2 (2013) - Schellevis, François G.
The epidemiology of multimorbidity, or multiple chronic conditions (MCCs), is one of the research priority areas of the U.S. Department of Health and Human Services (HHS) by its Strategic Framework on MCCs. A conceptual model addressing methodological issues leading to a valid measurement of the prevalence rates of MCCs has been developed and applied in descriptive epidemiological studies. Comparing these results with those from prevalence studies performed earlier and in other countries is hampered by methodological limitations. Therefore, this paper aims to put the size and patterns of MCCs in the USA, as established within the HHS Strategic Framework on MCCs, in perspective of the findings on the prevalence of MCCs in other countries. General common trends can be observed: increasing prevalence rates with increasing age, and multimorbidity being the rule rather than the exception at old age. Most frequent combinations of chronic diseases include the most frequently occurring single chronic diseases. New descriptive epidemiological studies will probably not provide new results; therefore, future descriptive studies should focus on the prevalence rates of MCCs in subpopulations, statistical clustering of chronic conditions, and the development of the prevalence rates of MCCs over time. The finding of common trends also indicates the necessary transition to a next phase of MCC research, addressing the quality of care of patients with MCCs from an organizational perspective and with respect to the content of care.